Strengthening student learning motivation through the strategic role of islamic education teachers in fiqh instruction at madrasah tsanawiyah negeri 2 sukoharjo - Arminda Juliana Sari (At Turots: Jurnal Pendidikan Islam, 2025)
This research aims to analyze the strategic role of Islamic Education (PAI) teachers in enhancing student learning motivation in the subject of Fiqh at Madrasah Tsanawiyah Negeri 2 Sukoharjo for the academic year 2023–2024. The primary focus of this study is to identify the factors influencing student learning motivation and the strategies employed by PAI teachers to enhance it. The research poses several questions: (1) What factors affect student learning motivation in Fiqh instruction? (2) What role do PAI teachers play in enhancing student learning motivation? This study employs a qualitative approach utilizing a case study method. Data were collected through in-depth interviews with teachers, students, and the head of the madrasah, as well as through observations of the learning process. The findings indicate that internal factors, such as the students' interest and religious needs, as well as external factors, including support from family and the madrasah environment, play significant roles in motivating students. Additionally, the strategies implemented by PAI teachers—such as personalized approaches, the use of engaging learning media, and the reinforcement of religious values—have proven effective in enhancing student learning motivation. These findings contribute significantly to the development of more motivating and relevant teaching methods for Fiqh that align with the needs of students in the madrasah.